Analysis of methods and means of text mining - Rybchak, Z.; Basystiuk, O. (Commission of Motorization and Energetics in Agriculture, 2017)
In Big Data era when data volume doubled every year analyzing of all this data become really complicated task, so in this case text mining systems, techniques and tools become main instrument of analyzing tones and tones of information, selecting that information that suit the best for your needs and just help save your time for more interesting thing. The main aims of this article are explain basic principles of this field and overview some interesting technologies that nowadays are widely used in text mining.
Keywords: text mining; text analytics; data analysing; high-quality information; text categorization; text clustering; document summarization; sentiment analysis